Production and Perception of Tone 3 Focus in Mandarin Chinese - Lee, Yong-Cheol; Wang, Ting; Liberman, Mark (Frontiers in Psychology, 2016)
This study uses production and perception experiments to explore tone 3 focus in Mandarin Chinese. Overall, contrastive focus in Mandarin is clearly marked with increased duration, intensity, and pitch range: in the experiments, listeners identified focused syllables correctly more than 90% of the time. However, a tone 3 syllable offers a smaller capacity for pitch range expansion under focus, and also yields less intensity increase; in addition, local dissimilation increases the duration, intensity, and pitch range of adjacent syllables within the same phrase as a focused tone 3 syllable. As a result, tone 3 focus was less well identified by listeners (77.1%). We suggest that the relatively poor identification of tone 3 focus is due to the smaller capacity for pitch range expansion, the confusion from within-phrase local dissimilatory effects, and the relatively weak intensity of tone 3. This study demonstrates that even within a language where purely prosodic marking of focus is clear, the location of prosodic focus can be difficult to identify in certain circumstances. Our results underline the conclusion, established in other work, that prosodic marking of focus is not universal, but is expressed through the prosodic system of each language.